2023
DOI: 10.1002/agr.21801
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' willingness to invest in mechanized maize shelling and potential financial benefits: Evidence from Tanzania

Abstract: Sub‐Saharan Africa has the least mechanized agriculture in the world due to various reasons including low effective demand at farm level, low policy attention, and ineffective mechanization strategies. However, the situation has changed since recently in favor of mechanization while limited empirical evidence is available on how mechanization can be enhanced among smallholder farmers. In this study, we explore farmers' willingness to invest in mechanization services by considering the group business model (GBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This assumption is supported by studies elsewhere in Africa (Fischer et al, 2021;Kotu et al, 2023). For instance, Kotu et al (2023) found that about 65% of smallholder farmers in their sample were willing to invest in mechanized maize shelling within the group business model while only about 10% of them would like to do so within the individual business model. groups agreed to provide two types of services to their members including shelling services at payment and loan services to those who need.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This assumption is supported by studies elsewhere in Africa (Fischer et al, 2021;Kotu et al, 2023). For instance, Kotu et al (2023) found that about 65% of smallholder farmers in their sample were willing to invest in mechanized maize shelling within the group business model while only about 10% of them would like to do so within the individual business model. groups agreed to provide two types of services to their members including shelling services at payment and loan services to those who need.…”
Section: Discussionmentioning
confidence: 65%
“…Despite acknowledging the importance and potential benefits of collective action in overcoming resource constraints and achieving better economies of scale, there is a scarcity of empirical evidence and comprehensive studies focusing on the conditions essential for the success of these collective initiatives, particularly in the domain of agricultural mechanization within smallholder farming communities. The existing literature provides insights into the advantages of mechanization in transforming agriculture and highlights the challenges faced by smallholder farmers in accessing mechanization services (Houssou et al, 2013;Diao et al, 2014;Fischer et al, 2021;Hodjo et al, 2021;Kotu et al, 2023). However, the specific factors that contribute to the success or failure of collective efforts in adopting mechanized maize shellers among these farmers remain underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…As would be expected given technological advances in farm equipment and the rise of precision agriculture, a fair amount of research (n = 49 articles) has focused on investments in equipment [38,42,97,98]. Interest in this topic has been fueled by the diversity of equipment and production systems, which each have distinct characteristics and applications, whether or not DTs are involved.…”
Section: Investments In Individual Factors Of Productionmentioning
confidence: 99%
“…These DTs function as independent pieces of equipment. Thus, their investment cost is equivalent to their purchase cost and can be evaluated using accounting classification criteria if amortization occurs [98,108,110,111].…”
Section: Figure 4 Main Categories Of Farm Equipment Investmentsmentioning
confidence: 99%
“…More specifically, agricultural mechanization using tractors has significant impacts on labor productivity (Hamilton et al, 2022), farm efficiency (Huan et al, 2022), off‐farm income (Nguyen & Warr, 2020), land productivity (Zheng et al, 2021; Zhou et al, 2020), farm income growth (Kotu et al, 2023; Takeshima, 2018), off‐farm employment (Ma et al, 2018), and voluntary employment (Zhou & Ma, 2021). Moreover, in a study conducted in Myanmar, for example, agricultural mechanization enabled farmers to have incremental, overlapping, and complementary advantages such as labor savings, reduced drudgery, convenience, increased speed and timeliness of operations, improved ability to manage weather‐related risks, and reduced loss of grain during harvesting (Belton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%